2019
DOI: 10.3390/jcm8081132
|View full text |Cite
|
Sign up to set email alerts
|

Catestatin in Acutely Decompensated Heart Failure Patients: Insights from the CATSTAT-HF Study

Abstract: The role of catestatin (CST) in acutely decompensated heart failure (ADHF) and myocardial infarction (MI) is poorly elucidated. Due to the implicated role of CST in the regulation of neurohumoral activity, the goals of the study were to determine CST serum levels among ninety consecutively enrolled ADHF patients, with respect to the MI history and left ventricular ejection fraction (LVEF) and to examine its association with clinical, echocardiographic, and laboratory parameters. CST levels were higher among AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 61 publications
2
27
0
8
Order By: Relevance
“…Furthermore, it has been reported to be a key regulator of cardiovascular function, with cardioprotective effects including exhibiting the trough suppression of atherosclerosis [21], negative inotropic and lusitropic cardiac effects [22], inhibition of coronary vasoconstriction [21], a reduction in oxidative stress in ischemic-reperfused myocardium [22], a decrease in endothelial inflammation and regulation of blood pressure [10,[23][24][25]. CST is believed to have an important role in the pathophysiology of hypertension, heart failure, reperfusion injury and coronary heart disease [25][26][27]. Intestinal inflammation has been associated with dysfunctional ChgA production [28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported to be a key regulator of cardiovascular function, with cardioprotective effects including exhibiting the trough suppression of atherosclerosis [21], negative inotropic and lusitropic cardiac effects [22], inhibition of coronary vasoconstriction [21], a reduction in oxidative stress in ischemic-reperfused myocardium [22], a decrease in endothelial inflammation and regulation of blood pressure [10,[23][24][25]. CST is believed to have an important role in the pathophysiology of hypertension, heart failure, reperfusion injury and coronary heart disease [25][26][27]. Intestinal inflammation has been associated with dysfunctional ChgA production [28].…”
Section: Introductionmentioning
confidence: 99%
“…These activities may give rise to the blood pressure-and heart rate-lowering functions of this endogenous peptide. Because CST is accepted as a part of the complex neurohumoral compensatory feedback system, higher levels of this peptide in peripheral blood might indirectly reflect increased neurohumoral burden [16]. However, it may be insufficiently compensatory when the level of CST increases in patients with APE.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was suggested that catestatin might be a novel marker reflecting LV remodelling in the myocardium following AMI [19]. Boravac et al found that among patients with acutely decompensated heart failure, serum catestatin levels were higher [16]. They explained that higher CST levels are associated with beneficial metabolic and cardioprotective effects, but high CST levels reflect higher disease severity and probably parallel increased neurohumoral activity that might translate to adverse outcomes during the natural course of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown increased catestatin concentrations in people with acute myocardial infarction [15][16][17][18]. In contrast to the acute course in human myocardial infarction, the common canine cardiac disease MMVD is characterized by a slow but progressive disease development, usually over several years, eventually leading to development of CHF in some dogs [20,23].…”
Section: Discussionmentioning
confidence: 99%